PENGARUH PEMBERIAN JUS STROBERI TERHADAP KADAR HEMOGLOBIN PADA MAHASISWA - Saroh, Dewi (Jurnal Farmasi (Journal of Pharmacy), 2023)
Student are one of the groups that are prone to suffer from anemia. Strawberries contain 60 mg of vitamin C. The increase in hemoglobin levels is influenced by the presence of vitamin C in the body. The purpose of this study was to determine the effec of strawberry juice consumption to hemoglobin levels.The research design used was experimental analytics with pretest and posttest approaches. The sampling technique used was purposive sampling. Sample of 28 female students at Level 1 DIII Medical Laboratory Technology. Examination of hemoglobin levels using the cyanmethemoglobin method with a Microlab 300 photometer.The results of this study obtained average hemoglobin levels before consuming 11.28 and after consuming 12.58. A total of 26 respondents increased hemoglobin levels, and 2 respondents decreased. The paired T test results obtained a p = 0.000 (p < 0.05). So it can be concluded that there is a significant influence of strawberry juice consumption on hemoglobin levels